FAKTOR RISIKO MOBILTAS PENDUDUK DENGAN KEJADIAN COVID-19 DI KOTA BAUBAU - Yanti Sutiani; Ramadhan Tosepu; Wa Ode Salma (NHM PRESS, 2021)
COVID-19 or SARS-CoV-2 is an infectious disease. The spread of Covid-19 is not only influenced by specific factors of the pathogen, it is also influenced by population structure and population mobility. Population mobility contributes to the spread of infectious diseases. Diseases can move from one region to another through population mobility, which can pose a serious threat to global health. Baubau City has specific local characteristics, namely as an island and a transit port city for the surrounding islands. To investigate the risk factors for the occurrence of COVID-19 in Baubau City in relation to population mobility variables and population mobility flexibility policies. Data on confirmed cases of COVID-19 in 43 Kelurahan Baubau City were collected and identified from the Baubau City Health Office. This study uses descriptive analysis to describe the characteristics of the Covid-19 incident. Risk factors for population mobility and population mobility flexibility policies contribute to and have a relationship with the incidence of COVID-19 in Baubau City. When the pandemic has spread widely, it is important to understand the various measures to control human mobility and transmission of the ovid-19 virus by responding to and combining various public health scenarios.